Challenges and Coping Strategies of School Administrators and Elementary Teachers During Pandemic - Barrera, Janet D.; Ursabia, Ricky T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This quantitative correlational study determined the challenges and the coping strategies during the pandemic of the 12 school administrators and 94 elementary teachers in Sindangan South I and II Districts, School Year 2020-2021. Specifically, it discussed the trainings and webinars attended; seriousness of the technological, financial and pedagogical challenges encountered; and acceptability of the coping strategies. A questionnaire-checklist was used and analyzed using five-point Likert scale. Reliability test using Cronbach alpha was determined using SPSS. The Mann-Whitney U and Spearman rho tests were used in statistical inference. The study disclosed that the school heads have set their highest priorities in preparing their constituents in times of eventualities, and security and health of the school’s stakeholders. Both groups of participants noted the serious challenges they encountered during the pandemic in terms of technology, financial and pedagogies. They had very acceptable coping strategies in terms of technological, financial and pedagogical challenges. The two groups of participants agreed on the challenges they encountered. They have conflicting views and perceptions on coping financial challenges. The trainings and webinars attended were not vital and contributory to their views on challenges. The acceptability of coping strategies was not associated with their attendance to trainings and webinars. The study recommends for the provision of trainings and webinars on ICT skills and utilization; better equip their schools with educational technology; strengthen collaboration with stakeholders; and future researches to venture on psychological factors contributing to teachers’ willingness to use technologies.